1990
DOI: 10.1007/bf02390664
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal prolactin in pregnancy-induced hypertension

Abstract: In plasma from 35 women with pregnancy-induced hypertension (PIH) and 35 normal pregnant women both at 39 weeks of gestation, plasma prolactin levels were measured at 8.30 a.m. (PRL1) and 9.30 a.m. (PRL2) under basal conditions. At delivery umbilical cord blood samples were taken for measurement of fetal prolactin (PRLF). PRL1 and PRL2 were higher in women with PIH, but no significant relations were found between PRL1/PRL2 and blood pressure. PRLF did not differ when infants of mothers with PIH and infants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…A higher rate of preterm delivery (28% versus 9% in the control group) (p=0.0003) was ascribed to maternal disease for which the drugs were prescribed. In two therapeutic trials of verapamil among hypertensive pregnant women, no adverse drug-related effects were observed among infants (79).…”
Section: Calcium Channel Blockersmentioning
confidence: 95%
“…A higher rate of preterm delivery (28% versus 9% in the control group) (p=0.0003) was ascribed to maternal disease for which the drugs were prescribed. In two therapeutic trials of verapamil among hypertensive pregnant women, no adverse drug-related effects were observed among infants (79).…”
Section: Calcium Channel Blockersmentioning
confidence: 95%
“…A study by Marlettini MG et al, also havereported higher plasma prolactin levels in women with pregnancy induced hypertension (PIH) at 39 weeks of gestation when compared to controls. 7 Similarly, Hayashi RH et al have reported the significant elevation of prolactin in PIH group in comparison to normal pregnancy only at the 37 to 39 gestational weeks interval but the difference did not reach the significant level when the overall value of 16-42 gestational weeks was compared. Pre-eclampsia is a placenta dependent disease exemplified by the fact that all the symptoms disappear after delivery.…”
Section: Discussionmentioning
confidence: 93%
“…12 Notably, these vasoinhibins have been associated with the endothelial cell dysfunction and compromised birth weight that characterize preeclampsia Though it has been proposed that prolactin causes rise in MAP based on rabbit studies, 13 the same might not hold true for humans as evidenced by poor correlation between MAP and serum prolactin in our study.This is in agreement with one of the studies that have shown a non-significant relationship between the blood pressure and the prolactin levels. 7 In this regard, serum prolactin is not a good indicator of severity of disease, based on its poor correlation with MAP and 24h UTP, which are established markers of the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal and cord blood prolactin level have been linked to pregnancy complications such as gestational diabetes, pregnancy induced hypertension, prematurity and respiratory distress syndrome 6,8-11. Most studies have concentrated on the role of cord blood prolactin in lung maturity.…”
Section: Introductionmentioning
confidence: 99%